2003
DOI: 10.1038/sj.ejcn.1601899
|View full text |Cite
|
Sign up to set email alerts
|

Effects on health of fluid restriction during fasting in Ramadan

Abstract: During the 9th month (Ramadan) of the Islamic calendar (Hijra) many millions of adult Muslims all over the world fast during the daylight hours. Since Hijra is a lunar calendar, Ramadan occurs at different times in the seasonal year over a 33-year cycle. Fasting during Ramadan is partial because the abstention from food, fluid, tobacco and caffeine is from sunrise to sunset. Several categories of people are exempt or can postpone the Ramadan fast. The effect on health and well being of the month-long intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
198
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(220 citation statements)
references
References 46 publications
8
198
3
1
Order By: Relevance
“…The majority of Indonesian people are Muslims, who are obliged to fast (total abstinence from food and drink) for as long as 14 h (from 0330 to 1730) each day for a month. Many studies have been conducted to evaluate the impact of Ramadan fasting on various aspects of health, including lipid metabolism (Fedail et al, 1982;El Arnoaty and Johnson, 1991;Adlouni et al, 1997), acute coronary heart disease and respiratory system (Temizhan et al, 1999;Ramadan and Barac-Nieto, 2000), water balance (Duncan et al, 1990;Schmahl and Metzler, 1991;Leiper et al, 2003;Basiri et al, 2004), dietary intake, endocrine function, serum fructosamine, and clinical, anthropometrical, and most biological parameters (Habbal et al, 1998;Perk et al, 2001;Beltaifa et al, 2002;Ramadan, 2002;Gharbi et al, 2003;Gustaviani et al, 2004;Kassab et al, 2004;Yucel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of Indonesian people are Muslims, who are obliged to fast (total abstinence from food and drink) for as long as 14 h (from 0330 to 1730) each day for a month. Many studies have been conducted to evaluate the impact of Ramadan fasting on various aspects of health, including lipid metabolism (Fedail et al, 1982;El Arnoaty and Johnson, 1991;Adlouni et al, 1997), acute coronary heart disease and respiratory system (Temizhan et al, 1999;Ramadan and Barac-Nieto, 2000), water balance (Duncan et al, 1990;Schmahl and Metzler, 1991;Leiper et al, 2003;Basiri et al, 2004), dietary intake, endocrine function, serum fructosamine, and clinical, anthropometrical, and most biological parameters (Habbal et al, 1998;Perk et al, 2001;Beltaifa et al, 2002;Ramadan, 2002;Gharbi et al, 2003;Gustaviani et al, 2004;Kassab et al, 2004;Yucel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In most situations where water turnover rate is altered, the total body water content is usually conserved 33 . In a recent study using an isotopic tracer technique in Malaysian Muslims 34 , it was demonstrated that total body water content was conserved during Ramadan although daily water turnover was reduced. The decrease in water turnover in this study appeared to be due to a reduction in recorded fluid intake, but hydration was maintained by a drop in non renal losses 35 .…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Leiper, Molla and Molla (2003) relative to food, the restriction on fluid intake during the fasting period directly impacts the regulation of body core temperature.…”
Section: Athlete D: "…Malaysia Is a Hot Country And We Train Under Tmentioning
confidence: 99%
“…sleep disturbances, general fatigue, and impairment of cognitive functions (Kadri et al, 2000;Leiper et al, 2003;Tian et al, 2012). Research related to Ramadan and performance in Malaysia have been helpful in understanding how Ramadan fasting affects sports performance (see Aziz & Weileen, 2008;Roy et al, 2011a;Roy et al, 2011b;Singh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%